Management systems of Don Mariano Marcos Memorial State University-sericulture research and development institute - Teneza, May Angelica M. (City of San Fernando, La Union : [s.n.], 2017)
This descriptive research assessed the extent of implementation of the management systems along marketing, operations, human resource, financial and research and development management; its capabilities and inadequacies; and the degree of seriousness of the problems encountered by Don Mariano Marcos Memorial State University-Sericulture Research and Development Institute. the study was conducted on January 2017 to 65 respondents. Data gathered using questionnaire were treated using arithmetic mean and ranking. The respondents were employees and officials from different departments. Financial statements analysis was also conducted by the researcher. The study found that the management systems in DMMMSU-SRDI were moderately implemented. The capabilities of the current management systems of DMMMSU-SRDI included wide variety of quality products, strict implementation of standards for quality products and attractive compensation packages. On the othe hand, inadequacies consisted of non-aggressive marketing strategies, non-strategic store location and limited channels of distribution. The problems/ constraints that hindered the achievement of its goals included inadequate promotional activities, non-strategic store location, outdated equipment and old buildings that need repairs, inadequate employee training and development, inefficient collection of receivables and limited budgets. A five-year strategic plan was formulated by the researcher and proposed for adoption to help the management to improve its operations.
Bibliography: pages 122-124.
CHED-La Union
Keywords: Personnel management